IMPROVING READING COMPREHENSION SKILLS USING THE DISCOVERY LEARNING METHOD ASSISTED BY COMIC STRIP MEDIA - Rozak, Dinda Luthfiana; Suhada, Dadang; Nuratikah, Nuratikah (Transpublika Publisher, 2024)
This research was conducted as a classroom action research project with the aim of enhancing the reading comprehension skills of fourth-grade students at MI Hidayatussibyan in Krangseng District, Indramayu Regency. The research utilized the discovery learning method, supported by the use of comic strip media. The main objective of this study was to benefit various stakeholders involved in the learning process, particularly in the Indonesian language subject. These stakeholders included teachers, students, schools, communities, and the wider education community. The research followed a classroom action research approach, consisting of two cycles that encompassed planning, action, observation, and reflection stages. The study took place at MI Hidayatussibyan during the 2021/2022 academic year, with a sample of 28 fourth-grade students as the focus of the research. Data collection was carried out through observation and documentation. Therefore, this research not only contributed to the advancement of learning methods but also provided valuable insights for educational practitioners and individuals involved in the learning process at the school.